Jurisprudential and Legal Principles and Rules Corresponding to the Obtaining of Evidence in Iranian Criminal Law Emphasizing the Procedure of the International Criminal Court - Mehdi Halalkhor Mirkola; Abbas Tadayyon; Rajab Goldoost Joubari (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The obtaining of evidence is one of the most important and fundamental subjects in Iranian criminal law and the International Criminal Court. According to it, without evidence, it is not possible to detect a crime and attribute the crime to the accused and to execute punishment and acquit the perpetrator. Among the most important principles governing the obtaining of evidence in Iranian criminal law and the International Criminal Court, we can name the principle of legitimacy of obtaining of evidence, the presumption of innocence, the principle of free evaluation of evidence, the principle of freedom of obtaining of evidence, and the principle of legality of evidence that non-observance of these principles and obtaining of evidence through illegitimate ways is not only against human rights and the dignity of humans and the administrators of justice but also causes a reversal of the verdict in the Court of Appeal. Although there are no clear provisions in Iranian criminal law in this regard, in the procedure of the International Criminal Court, non-observance of those principles is one of the reasons for the invalidity of the investigation process. This article tries to deal with different aspects of this subject and provide solutions to that.